Electronic absorption study on acid-base equilibria for some keto and thioketo pyrimidine derivatives - Experimental and theoretical evidence of enolization and solute-solvent interactions - KILIÇ, HASAN (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
The UV-vis spectra of recently synthesized 1-amino-5-benzoyl-4-phenyl-1H-pyrimidine-2-one, (I), and 1-amino-5-benzoyl-4-phenyl-1H-pyrimidine-2-thione (11), were studied in aqueous methanol (5%, v/v, methanol) and pure methanol. The nature of the electronic transitions and the role of carbonyl oxygen of I and thiocarbonyl sulfur of II in the behavior of the observed UV-vis spectra were discussed. The carbonyl group at position 2 of I and the thiocarbonyl group of II were found to be enolized instead of protonation. Quantum chemical calculations showed agreement with the experimental evidence. However, the carbonyl group of the benzoyl moiety at position 5 of both compounds underwent neither enolization nor protonation. Acid-base equilibria of the compounds against varying pH have been examined in detail. The pK(a) values of all related equilibria were determined at room temperature and an ionic strength of 0.10 M from the pH-dependence of the absorbance values using the Henderson-Haselbalch equation and graphical logarithmic analysis. The mean acidity constants for the protonated forms of the compounds were determined as pK(a1) =4.214 and pK(a2) = 6.678 for I and pK(a1) = 3.739 and pK(a2) = 6.258 for II. The mean acidity constants (pK(a3)) for the enol form of I and the thioenol form of II were determined as 11.278 and 11.063, respectively. The preferred dissociation mechanisms were discussed based on the data of UV-vis spectroscopy and a mechanism was proposed for each compound. The formation of intramolecular and intermolecular hydrogen bonding were found with I but not with II. The intramolecular bonding stabilizing the enol form was favoured at pH values corresponding to pK alpha 1 and above. On the other hand, the intermolecular hydrogen bonding stabilizing the free form of the carbonyl group was favoured at all pH values. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: hydrogen bonding interactions; acidity constant; enolization; carbonyl; thiocarbonyl; UV/vis spectroscopy; REFERENCE VALUE STANDARDS; DISSOCIATION-CONSTANTS; OXALYL COMPOUNDS; PH MEASUREMENTS; WATER; MIXTURES; TAUTOMERISM; PROTONATION; IONIZATION; COMPLEXES